Workers' participation in managerial decision-making : a study in a developing country - Mannan, M. A. (Mohammad Abdul) 1950- (New Delhi : Daya Pub. House, 1987)
Relates to industrial management in Bangladesh.
Revision of the author's thesis (Ph. D.--Delhi University, 1984)
Includes index.
Includes bibliographical references and index.
Keywords: Industrial management -- Employee participation -- Bangladesh; Industrial management -- Bangladesh -- Decision making